Effect of Different Metal Ions on the Biological Properties of Cefadroxil - Reinhard H. H. Neubert; Cornelia Große; Yahya Mrestani; Matthias Brandsch; Beate Bretschneider; Sayed H. Auda; Ilka Knütter (MDPI AG, 2009)
The effect of different metal ions on the intestinal transport and the antibacterial activity of cefadroxil [(6R,7R)-7-{[(2R)-2-amino-2-(4-hydroxyphenyl)acetyl]amino}-3-methyl-8-oxo-5-thia-1-azabicyclo[4.2.0]oct-2-ene-2-carboxylic acid] was investigated. The [14C]Gly-Sar uptake via PEPT1 was inhibited by Zn2+ and Cu2+ treatment in a concentration-dependent manner (Ki values 107 ± 23 and 19 ± 5 μM, respectively). Kinetic analysis showed that the Kt of Gly-Sar uptake was increased 2-fold in the presence of zinc sulphate (150 μM) whereas the Vmax value were not affected suggesting that zinc ions inhibited Gly-Sar uptake by PEPT1 in a competitively manner. Ni2+ exhibited moderate inhibitory effect, whereas Co2+, Mg2+, Al3+ ions showed no inhibitory effect on Gly-Sar uptake via PEPT1. Subsequently, we examined the effect of Zn2+ and Al3+ ions on the transepithelial transport of cefadroxil across Caco-2 cells cultured on permeable supports. The results showed that zinc ions inhibited the transepithelial flux of cefadroxil at Caco-2 cell monolayers while Al3+ ions had no effect. The interaction of cephalosporins with the metal ions could suggest negative effects of some metal ions on the clinical aspects of small intestinal peptide and drug transport. Finally, the effect of Zn2+, Cu2+ and Al3+ ions on the antibacterial activity of cefadroxil was tested. It was found that there is no significant difference between the activity of cefadroxil and the cefadroxil metal ion complexes studied against the investigated sensitive bacterial species.